Considerations about the first book of thermal springs in Costa Rica - Vargas, Asdrúbal G. (2015)
In this work is presented the translation and considerations about the first full catalog with twenty five thermal springs described by A. v. Frantzius in Costa Rica. Since the first publication on hot springs came out incomplete as an article in a medical journal, von Frantzius was given the task of publishing their research through a book in the nineteenth century, with the description of the hot springs in the Reventazón river basin near to Cartago (then the capital of Costa Rica) and in the Candelaria river basin southwestern from San José. The descriptions made in these catalog refer to hot springs located in areas geologically formed by no volcanic rocks or near ancient extinct volcanic apparatus. Frantzius described the geographical and geological characteristics of the places where hot springs emerge and divided them into three groups located in river Reventazón, Candelaria and Grande river basins and Guanacaste region. In eleven hot springs measured the temperature, and determined that the spring with higher temperature was Barranca, while the lowest temperature was Tres Ríos. He proposes a relationship between the topographic elevation of the surface of terrain where the spring emerged and temperature of the water in the thermal spring. He also examined the concentration of several chemical compounds from hot spring Agua Caliente de Cartago.